Faktor - Faktor yang Berhubungan dengan Mengkonsumsi Makanan yang Mengandung Bahan Pengawet pada Anak SDN 2 Kecamatan Dangia Kabupaten Kolaka Timur Tahun 2016 - Masriwati, Sitti (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2016)
Based on a survey conducted on 10 children, they said they liked to eat snacks in the school environment, often snacked because their parents were given pocket money, often snacked without paying attention to the expiration date and the content contained in the snack packaging, and often snacked at school even though they were provided with food. from home by his parents. The purpose of this study was to determine the factors associated with consuming foods containing preservatives. This type of research is an analytic study with a cross sectional research design. The population in this study was 96 people, with a sampling technique using a proportional stratified random sampling technique, with a total sample of 48 people. The method of analysis used Chi Square statistical test and continued with the phi coefficient test. The results showed that there was a moderate relationship between food behavior with a value of > (6.680> 5.591) with a phi coefficient test with the result = 0.37, there was a moderate relationship between pocket money with a value of > (9,833> 5.591) with a phi coefficient test with the result = 0.45, there is a moderate relationship between nutritional knowledge with a value of > (6.701> 5.591) with a phi coefficient test with a result = 0.47, there is a very strong relationship between snack preferences with a value of > (42.488> 5.591) with a phi coefficient test with a result = 0.94, there is a strong relationship between peer influence with a value > (14,742 > 5,591) with a phi coefficient test with a result = 0.55, by consuming foods that contain preservatives. It is recommended that parents control the consumption of food containing preservatives in children by reducing the amount of food containing preservatives circulating in the school canteen.